CARING FOR CAREGIVERS Family caregivers of patients with chronic illness (2019)
Caring for caregivers, family caregivers of patients with chronic illness; this research is aimed to those nursing students and professionals, who are interested in getting to know standards of care, as well as those who are responsible of patients with chronic illness. This experience implies challenges, difficulties, and special requirements, which generate special care programs - through other people´s experiences, analysis of literature, and research-. This book is based on the Caring for caregivers Program, designed by a group of Professors at Universidad Nacional de Colombia, School of Nursing, aimed to strengthen those caregivers abilities to care. Thus, the key features that contributed to the creation and development of the program are set out throughout this book. Participant´s names have been changed to help preserve anonymity.